Rembuk Blok dan Tepo Seliro: Menegakkan Harmoni Melalui Nilai Hukum Adat di Rutan Jepara - Firdaus Falaq; Navis Nailil Munna (Jurnal Hukum Lex Generalis, 2025)
This study examines the integration of Javanese customary values (rembuk blok and tepo seliro) in conflict resolution among inmates at Jepara Detention Center as an alternative to seclusion-based sanctions. Using critical ethnography (2023-2024) with participatory observation, interviews with inmates and prison officer, and analysis of conflict cases, findings reveal: (1) rembuk blok prevents conflict escalation through participatory dialogue; (2) tepo seliro facilitates empathy-based reconciliation; (3) adaptation of customary social sanctions (voluntary exclusion) improves social cohesion. Key barriers include philosophical gaps between state-customary law, staff resistance, and regulatory voids. Recommendations include integrating rembuk blok into conflict mediation SOPs and legal pluralism-based staff training.